Participation, knowledge, and attitudes toward cervical cancer screening among migrant Burmese women on China-Myanmar border: a cross-sectional study - Jiawei Hu; Honghao Wang; Shuang Zhao; Liuye Huang; Xiaoqing Chen; Xuelian Zhao; Yong Zhang; Fanghui Zhao (Preventive Medicine Reports)
Objective: This study aimed to investigate cervical cancer screening participation, knowledge of cervical cancer and screening, attitudes toward relevant healthcare services, and associated factors among migrant Burmese women in Mangshi, a county on the China-Myanmar border in Southwest China's Yunnan province. Methods: A cross-sectional study was conducted in Mangshi Maternal and Child Health Hospital from October 2020 to December 2021. Migrant Burmese women attending routine gynecological examinations were recruited via convenient sampling. An interviewer-administered questionnaire was utilized to collect data. Logistic regressions were utilized to assess factors associated with cervical cancer screening participation and knowledge level. Results: Among 1504 participants, 31.3 % ever attended cervical cancer screening. In the recommended age group of 25–64 years, the participation rate was 35.2 %. Screening participation was associated with age, marital status, occupation, and history of genital tract infection. Approximately 20.9 % had heard of human papillomavirus, 23.2 % knew cervical cancer is preventable, and 41.6 % had heard of cervical cancer screening. Awareness of risk factors, screening techniques, and symptoms was limited. The median knowledge score was 2.0 out of 19.0. Knowledge level was associated with education, age at menarche, number of sexual partners, and history of genital tract infection. Most (99.7 %) participants were willing to attend cervical cancer screening, but only 84.5 % would accept therapy if necessary. The most common barrier to therapy was unaffordable cost. Conclusions: Migrant Burmese women in Mangshi had suboptimal screening participation and inadequate cervical cancer knowledge. Screening policies should prioritize socioeconomically disadvantaged women. Enhancing targeted health education is essential.